The Interior Design of Сinema “Hoktember” in Gyumri - Mikayelyan, Ruzanna (History and Culture, 2021)
The purpose of this article is to unveil solutions used for the interior of Cinema “Hoktember” (in Gyumri), which is of historical and cultural value, to explain and analyze its stylistic, ergonomic, zoning, redesign, compositional, and formal features. The research also re-visits the chronology of the cinema style changes and phases as well as analyzes the baseline points and the current situation of the building. The research is anchored on historic, analytic and comparative methods in terms of appreciation of experience of the past, and henceforth for future implementation of exact design and proper construction and organization of spectating space of such buildings. It is also important for maintenance, preservation and rehabilitation of similar type of buildings of historic value.